2016
DOI: 10.12740/app/66485
|View full text |Cite
|
Sign up to set email alerts
|

Patients’ perceptions of treatment credibility and their relation to the outcome of group CBT for depression

Abstract: SummaryBackground: While there has been some evidence supporting the relevance of patients' perceptions of treatment credibility to the process and outcome of individual cognitive-behavioral therapy (CBT), its importance to group CBT remains unknown. Moreover, no studies to date have explored potential mechanisms through which perceived treatment credibility may contribute to therapeutic change.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 43 publications
2
5
0
Order By: Relevance
“…In the convergent validity, the association between the CEQ credibility factor and the therapeutic alliance in session 2 was not statistically significant in the present study (Marôco, 2014). However, previous research suggests that credibility and expectation are associated with the therapeutic relationship and these processes may influenced each other throughout therapy (Ametrano, 2011;Smeets et al, 2008;Sochting et al, 2016). It is possible, though, that the present results may be explained by the fact that the alliance was considered here (assessed through the WAI) during the initial sessions, when the relationship is still being established (Ardito & Rabellino, 2011).…”
Section: Discussionmentioning
confidence: 66%
See 2 more Smart Citations
“…In the convergent validity, the association between the CEQ credibility factor and the therapeutic alliance in session 2 was not statistically significant in the present study (Marôco, 2014). However, previous research suggests that credibility and expectation are associated with the therapeutic relationship and these processes may influenced each other throughout therapy (Ametrano, 2011;Smeets et al, 2008;Sochting et al, 2016). It is possible, though, that the present results may be explained by the fact that the alliance was considered here (assessed through the WAI) during the initial sessions, when the relationship is still being established (Ardito & Rabellino, 2011).…”
Section: Discussionmentioning
confidence: 66%
“…Regarding discriminant validity, no significant association was found between CEQ and clinical symptoms. Prior research on this issue is not consistent; however, there are several previous studies that also did not find a correlation between the symptoms and the credibility and expectation (Devilly & Borkovec, 2000;Smeets et al, 2008;Sochting et al, 2016;Thompson-Hollands et al, 2014). Nevertheless, the absence of a significant correlation between CEQ and clinical measures targeting mental health symptoms are within the expected results of a discriminant analysis, giving further support to the use of a 5-item version in the Portuguese context.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…Others have suggested that patient-perceived treatment credibility may facilitate the formation of a stronger therapeutic alliance, which in turn predicts treatment outcomes (Söchting, Tsai, & Ogrodniczuk, 2016). Although several studies have supported the association between higher treatment credibility and more positive alliance (Horvath & Greenberg, 1989; Söchting et al, 2016; Westra, Constantino, Arkowitz, & Dozois, 2011), the one study that formally tested the full mediational pathway failed to detect an indirect effect of credibility on outcome through alliance (Söchting et al, 2016). Consequently, this particular mediational pathway requires further testing.…”
Section: Moderators and Mediatorsmentioning
confidence: 99%
“…5 Failing to take this into consideration could bias the overall treatment effect estimate either up-or downwards. 6,7 Subgrouping pain patients with chronic pain such as NS CLBP is an important way to provide support for health care systems to optimize resources and costs 8 .…”
Section: Introductionmentioning
confidence: 99%